PENCEGAHAN DAN PENANGGULANGAN KEBAKARAN HUTAN DAN LAHAN DI KOTA PALANGKA RAYA (STUDI DI DINAS KEHUTANAN DAN PERKEBUNAN KOTA PALANGKA RAYA) - DELIMA YOSEPINE.S LUMBANTOBING; Nurul Hikmah (Universitas Palangka Raya, 2020)
The objective of the research was to describe and to analyze the evaluation on the Regional Regulation No. 07/2003 on Handling and Forestalling Forest and Land Fire in Palangka Raya, based on the Evaluation Theory on Policy of William Dunn, viewed from effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy, along with reinforcing and inhibiting factors in the implementation of the policy. Forest and land fire has become one of the disasters occurred in Palangka Raya. It usually occurs in every dry season because in this season the people in Palangka Raya have an opportunity to clear new land. In clearing new land, people usually burn the land in order to save money and energy. They do it without getting permission from the government; therefore the government issues the Regional Regulation No. 07/2003 on Forestalling and Handling Forest and Land Fire. The implementation of this Regulation is handed down to the Forestry and Plantation Service of Palangka Raya and collaborates with villages in Palangka Raya. The research used descriptive qualitative method. It was conducted at the Forestry and Plantation Service Office of Palangka Raya. Primary data were obtained from the Forestry and Plantation Service Office of Palangka Raya (now it is the Environment and Forestry Service Office) of Palangka Raya and Kelurahan Bukit Tunggal. Secondary data were RT 04 RW 14 at Kelurahan Bukit Tunggal. The gathered data were analyzed by using Miles Huberman model based on data reduction, display data, and conclusion drawing/verification.The result of the research showed that the implementation of the Regional Regulation No. 07/2003 on Forestalling and Handling Forest and Land Fire in Pakangka Raya was not only performed by the Provincial Government, in this case the Forestry and Plantation Service Office of Palangka Raya, but also by collaborating with Villages in Palangka Raya.